1717. Relationship between Neighborhood Census-tract Level Poverty and Respiratory Syncytial Virus (RSV)-associated Hospitalizations in U.S. adults, 2015-2017. (31st December 2020) - Holmen, Jenna; Reingold, Art; Bye, Erica; Kim, Lindsey; Anderson, Evan J; Bennett, Nancy M; Chai, Shua; Kirley, Pam Daily; Muse, Alison; Talbot, Helen; Monroe, Maya; Rothrock, Gretchen; et al.
Abstract: Background: In the U.S., RSV is increasingly recognized as a cause of hospitalization for adults with respiratory illness. In adults > 50 years of age, it accounts for up to 12% of medically-attended acute respiratory illnesses and has a case fatality proportion of 6–8%. Poverty can have important influences on health on both the individual level as well as the community level. Few studies have evaluated the relationship of RSV and poverty level, and no identified studies have evaluated this relationship among adults. We evaluated the incidence of RSV-associated hospitalizations in adults across multiple sites in the U.S. by census-tract (CT) level poverty. Methods: Medical record data abstraction was conducted for all adults with a laboratory-confirmed RSV infection admitted to a hospital within the Centers for Disease Control and Prevention's Emerging Infections Program catchment areas within California, Georgia, Maryland, Minnesota, New York, and Tennessee during the 2015–2017 RSV seasons (October-April). Patient addresses were geocoded to their corresponding CT. CTs were divided into four levels of poverty, as selected in prior publications, based on American Community Survey data of percentage of people living below the poverty level: 0–4.9%, 5–9.9%, 10-19.9%, and ³20%. Incidence rates were calculated by dividing the number of RSV cases in each CT poverty-level (numerator) by the number of adults living in each CT poverty level (denominator), as determined from the 2010 US census, and standardized for age. Results: There were 1713 RSV case-patients with demographic characteristics (Table 1). The incidence of RSV-associated hospitalizations of adults increased with increasing CT level poverty (Figure 1 and Table 2). The risk of RSV-associated hospitalization was 2.58 times higher in census tracts with the highest (20%) versus the lowest (< 5%) percentages of individuals living below the poverty level. Table 1: Demographic characteristics of adults with an RSV-associated hospitalization, 2015-2017. Figure 1. Age-adjusted incidence rate of RSV-associated hospitalizations of adults by census-tract poverty level, 2015-2017 Table 2. Incidence rate ratios for RSV-associated hospitalizations of adults by census-tract poverty level, 2015-2017. Conclusion: The incidence rate of RSV-associated hospitalization in adults appears to have a positive association with increasing CT level of poverty; however, this trend reached significance only among cases living in CTs with higher percentages of poverty (≥ 10%). Disclosures: Evan J. Anderson, MD, Sanofi Pasteur (Scientific Research Study Investigator)